Annona deceptrix as a potential biofactory for secondary metabolites using plant cell and tissue cultures (Scientia Agropecuaria, 2025)
Plant biotechnology is a powerful tool that has enabled the transformation of plant cells into small-scale biofactories to produce secondary metabolites. These compounds can be synthesized in laboratory settings on a large scale, independent of spatial, resource, or environmental constraints. Identifying plant species with promising phytochemical profiles is crucial to obtaining bioactive products with high market demand and commercial value. The purpose of the present review is to highlight the potential of Annona deceptrix as a biotechnological resource, based on findings from previous studies conducted on other Annona species. Despite belonging to a botanical family with a well-established track record in the production of characteristic and biologically active secondary metabolites—particularly those with agrochemical relevance—A. deceptrix remains underutilized and understudied. Exploring its biotechnological potential is essential, as establishing this species in vitro would allow the development of callus production protocols, characterization of its cell growth kinetics, and the subsequent extraction of high-quality bioactive compounds. These extracts could serve as innovative solutions to challenges across various industries, ultimately leading to the development of marketable final products.
Keywords: Annonaceae; bioactive compounds; callus cultures; cell suspension cultures; biofactory